Islamic modernists and discourse on reason as a reconciliatory argument between Islam and the Western Enlightenment - Asmahan Sallah, (Universiti Kebangsaan Malaysia, 2015)
This article examines the debates on the relationship between Islam and reason during the nineteenth century and early twentieth century. It argues that these debates were transnational but were largely influenced by similar debates in the Western tradition. It also affirms that modernists used discourse on reason to reconcile Islam with Western Enlightenment. The article illustrates the various mechanisms which Islamic modernists implemented to facilitate such reconciliation. These mechanisms include rationalization of miracles, contesting the concept of prophethood, and rejecting the scholarship of Islamic jurisprudence and theology. Based on writings by several Islamic modernists, such as their biographies of Prophet Muhammad, Quran commentaries, and magazine articles in different Islamic countries, I ascribe these mechanisms to a gap between logic and experimental thought, a gap which seeped into the mind of Islamic modernists under the influence of Western contemporary thinkers. While this discourse claims compatibility between Islam and Western Enlightenment, it also resists the binary of the sacred and the secular, a major legacy of the Western Enlightenment.